Sosialisasi Tanggap Bencana Gempa Bumi Di SD Negeri 6 Kendari, Kota Kendari Tahun 2024 - Ndariani, Uci; Karimuna, Siti Rabbani; Risti; Rara, Seltiona Tiku; Amir, Setriyalin Putri; Safitra, Salwa; Rahmawati, Siti; Nur, Sitti Amalia; Maemuna, Nurmut; Meyitia, Sabrina Wahyuni; Sakriani; Wati, Siti Nurselfina; Aurin, Wa Ode Liska Nur (Jurnal Pengabdian Masyarakat (JUDIMAS), 2025)
An earthquake is a vibration on the earth's surface that occurs due to the sudden release of energy from within the earth which causes a change in the position of the earth. Based on Indonesian Disaster Information Data (DIBI), an average of ten disaster events occurred per day in Indonesia between 2019 and 2022. In 2021, Southeast Sulawesi Province was categorized as having high risk with a disaster risk index of 157.90, while Kendari City included in the medium risk category with an index of 116.50. This socialization aims to increase the awareness, knowledge and skills of SD Negeri 6 Kendari students in dealing with emergency situations in order to protect themselves and the environment. Activities are carried out through earthquake disaster response education which is measured by pre-test and post-test. The results of descriptive analysis show that the level of student knowledge before counseling was 6.62% and increased to 8.47% after counseling. The Wilcoxon test produces a Value of p = 0.000 (p <0.005), which shows that this education is effective in increasing students' knowledge about earthquakes.